INTERPRETING IN CRIMINAL CASES IN JAPAN: PAST, PRESENT, AND FUTURE PROSPECTS - MIZUNO, Makiko (Comparative Legilinguistics, 2019)
In the extant literature in Japan, the description of criminal cases involving foreigners goes back to around the fifth century; however, detailed depictions of language problems requiring legal interpreters started to appear in the Edo period (1603–1868). The cases of an Italian missionary who entered Japan illegally in 1709 and the robbery of Ainu graves by British consular officers in 1865 presented communication difficulties between the interrogator and accused in criminal procedures. This is common even today. This paper introduces the history of legal interpreting with reference to high profile cases, and reviews changes in communication issues in criminal proceedings involving non-Japanese speaking defendants in modern Japan. It also presents prospects regarding the shift in attitude among legal practitioners toward legal interpreting against the backdrop of recent judicial reforms including the introduction of a lay judge system and visualisation of the investigation process.